PENGEMBANGAN LKPD BERBASIS KEARIFAN LOKAL SUKU ROTE UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SD NEGERI OETEAS - Ndolu, Rasty Mardiwati Crisna; Nitte, Yulsy Marselina; Nahak, Kristina E. Noya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of Pancasila Education students in grade V of SD Negeri Oeteas and the use of LKPD that is not yet based on local wisdom. Learning that is still theoretical and less contextual causes students to experience difficulties in understanding the material of mutual cooperation in the surrounding environment. This study aims to determine the level of feasibility, practicality, attractiveness, and effectiveness of LKPD based on the local wisdom of the Rote Tribe in improving the learning outcomes of Pancasila Education for grade V students of SD Negeri Oeteas. The type of research used is Research and Development (R&D) with the ADDIE development model which includes the Analysis, Design, Development, Implementation, and Evaluation stages. The research instruments are in the form of validation questionnaires for subject matter experts, linguists, media experts, teacher and student response questionnaires, and learning outcome tests. The results of the study showed that the LKPD based on the local wisdom of the Rote Tribe was declared very feasible based on the validation of 100% of material experts, 100% of linguists, and 80.76% of media experts. The teacher's response obtained a percentage of 89.28% and the student response of 95.21% with the very good category. Student learning outcomes increased from a pretest score of 51.87% to 92.12% in the posttest. The average increase test result (N-Gain) of 0.8434 is in the high category. Thus, LKPD based on the local wisdom of the Rote Tribe is declared feasible, practical, interesting, and effective to be used in learning Pancasila Education to improve student learning outcomes.